Is the Hong Kong Stock Market Asymmetrical in Behavior? - Liew, Venus Khim-Sen; Chia, Ricky Chee-Jiun; Syed Azizi Wafa, Syed Khalid Wafa (EconBiz, 2015)
This study uncovers that there exists asymmetrical market reaction on the positive and negative news by the TGARCH, EGARCH and EGARCH – M models.Thus, investors could use the calendar anomaly in terms of asymmetrical behavior information to avoid and reduce the risk when investing in the Hong Kong stock market.